Nonintubated versus intubated thoracoscopic bullectomy for primary spontaneous pneumothorax: A multicenter propensity-matched analysis. (November 2022) - Elkhouly, Ahmed G; Karamustafaoglu, Yekta Altemur; Galvez, Carlos; Rao, Madhuri; Lerut, Philip; Grimonprez, Annelies; Akar, Firas Abu; Peer, Michael; Bedetti, Benedetta; Tosi, Davide; Turna, Akif; Elkahwagy, Mohamed; et al.
Background: We aimed at comparing in a multicenter propensity-matched analysis, results of nonintubated versus intubated video-assisted thoracic surgery (VATS) bullectomy/blebectomy for primary spontaneous pneumothorax (PSP). Methods: Eleven Institutions participated in the study. A total of 208 patients underwent VATS bullectomy by intubated (IVATS) (N = 138) or nonintubated (NIVATS) (N = 70) anesthesia during 60 months. After propensity matching, 70 pairs of patients were compared. Anesthesia in NIVATS included intercostal (N = 61), paravertebral (N = 5) or thoracic epidural (N = 4) block and sedation with (N = 24) or without (N = 46) laryngeal mask under spontaneous ventilation. In the IVATS group, all patients underwent double-lumen-intubation and mechanical ventilation. Primary outcomes were morbidity and recurrence rates. Results: There was no difference in age (26.7 ± 8 vs 27.4 ± 9 years), body mass index (19.7 ± 2.6 vs 20.6 ± 2.5), and American Society of Anesthesiology score (2 vs 2). Main results show no difference both in morbidity (11.4% vs 12.8%; p = 0.79) and recurrence free rates (92.3% vs 91.4%; p = 0.49) between NIVATS and IVATS, respectively, whereas a difference favoring the NIVATS group was found in anesthesia time ( p < 0.0001) and operative time ( p < 0.0001), drainage time ( p = 0.001), and hospital stay ( p < 0.0001). There was no conversion to thoracotomy and no hospital mortality. One patient in the NIVATS group needed reoperation due to chest wall bleeding. Conclusion: Results of this multicenter propensity-matched study have shown no intergroup difference in morbidity and recurrence rates whereas shorter operation room time and hospital stay favored the NIVATS group, suggesting a potential increase in the role of NIVATS in surgical management of PSP. Further prospective studies are warranted.